2017
DOI: 10.1242/dev.143297
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of Grainy head targets in Drosophila reveals regulatory interactions with the POU-domain transcription factor, Vvl

Abstract: Grainy head (Grh) is a conserved transcription factor (TF) controlling epithelial differentiation and regeneration. To elucidate Grh functions we identified embryonic Grh targets by ChIP-seq and gene expression analysis. We show that Grh controls hundreds of target genes. Repression or activation correlates with the distance of Grh-binding sites to the transcription start sites of its targets. Analysis of 54 Grh-responsive enhancers during development and upon wounding suggests cooperation with distinct TFs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 73 publications
3
26
0
Order By: Relevance
“…4 H), corroborating the notion that Yki is a transcriptional activator of Alas. Interestingly, duox mRNA, which encodes an enzyme that catalyzes the oxidation of two tyrosines to di-tyrosine (Edens et al, 2001) and which is also expressed in developing tracheae (Yao et al, 2017) did not show any significant difference in yki mutants ( Fig. 4 H).…”
Section: Yorkie Is Required For Proper Cross-linking Of Tracheal Apicmentioning
confidence: 96%
“…4 H), corroborating the notion that Yki is a transcriptional activator of Alas. Interestingly, duox mRNA, which encodes an enzyme that catalyzes the oxidation of two tyrosines to di-tyrosine (Edens et al, 2001) and which is also expressed in developing tracheae (Yao et al, 2017) did not show any significant difference in yki mutants ( Fig. 4 H).…”
Section: Yorkie Is Required For Proper Cross-linking Of Tracheal Apicmentioning
confidence: 96%
“…HMGB1/2 [128,129] Grh Die at embryo stage, no homeotic phenotype [130] Enhance Sce [108] Grainy head DNA binding domain (T/C)NAAC(C/T)GGT(T/C)(T/C)TGCGG [131]. Genome-wide consensus [132]. CP2 [133] Z Viable and fertile, no homeotic phenotype [134] Myb/SANT-like DNA binding domain (c/T)GAG(C/T)G [135]; genome-wide consensus [136].…”
Section: Dsp1mentioning
confidence: 99%
“…The Grh family of transcription factors is essential in defining epithelial cell fate (Boglev et al, 2011;Bray and Kafatos, 1991;Bray et al, 1988;Bray et al, 1989;Hemphälä et al, 2003;Nevil et al, 2017;Rifat et al, 2010;Traylor-Knowles et al, 2010;Uv et al, 1994;Uv et al, 1997;Wang and Samakovlis, 2012;Wilanowski et al, 2002;Yao et al, 2017). Grh proteins are highly conserved, with members found in all metazoans examined to date and with more distant relatives found in fungi (Paré et al, 2012;Traylor-Knowles et al, 2010;Venkatesan et al, 2003;Wang and Samakovlis, 2012;Wilanowski et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Grh proteins are highly conserved, with members found in all metazoans examined to date and with more distant relatives found in fungi (Paré et al, 2012;Traylor-Knowles et al, 2010;Venkatesan et al, 2003;Wang and Samakovlis, 2012;Wilanowski et al, 2002). Extensive work in Drosophila and mammalian cell culture has demonstrated that Grh acts to define an epithelial gene regulatory network during metazoan development (Boglev et al, 2011;Bray and Kafatos, 1991;Chen et al, 2016;Gao et al, 2013;Hemphälä et al, 2003;Nevil et al, 2017;Nishino et al, 2017;Senga et al, 2012;Wang and Samakovlis, 2012;Yao et al, 2017). More recently, Grh has been shown to have pioneerfactor activity, as it is required to maintain chromatin accessibility at enhancers in Drosophila eye imaginal discs and can poise these enhancers for transcriptional activation (Jacobs et al, 2018).…”
Section: Introductionmentioning
confidence: 99%